تسيير الموارد البشرية في الجامعة الجزائرية - أكرور، ميريام Akrour, Miriam; عبدالحميد، أمير محمد سمير محمد (جامعة عمار ثليجي الأغواط - كلية الحقوق والعلوم السياسية, 2022)
تهدف هذه الدراسة إلى التعرف على بعض المفاهيم ذات الصلة بتسيير الموارد البشرية، بدء من المصطلحات المكونة لها إلى المعنى والمضمون التقليدي والحديث لها وكذا وظائفها الأساسية وأهدافها، بغية بلورة ترجمة قريبة لمعناها وضبط مفهوم شامل لها ومن ثم التطرق إلى تسيير الموارد البشرية في الجامعة الجزائرية، باعتبارها أهم مؤسسات الدولة والتي تعول عليها مخططات الحكومة من أجل النهوض بالاقتصاد الوطني والمساهمة في حفظ مكونات الهوية الوطنية ناهيك عن نشر العلم والمعرفة وفي سبيل تحقيق التطور والازدهار ومسايرة التغيرات العالمية، ومما لا شك فيه أن أهم وسائلها في سبيل تحقيق ما ذكرناه الموارد البشرية التي تسير وفقا لأحكام قانونية وتنظيمية، بدء من التوظيف إلى التكوين فتسيير المسار المهني إلى غاية إنهاء العلاقة الوظيفية. This study aims to identify some concepts related to the management of human resources, starting from the terms that make up them to the traditional and modern meaning and content of them, as well as their basic functions and objectives, in order to crystallize a close translation of their meaning and set a comprehensive concept for them, and then address the management of human resources in the Algerian University. As the most important state institutions on which government plans depend in order to advance the national economy and contribute to preserving the components of national identity, not to mention the dissemination of science and knowledge, in order to achieve development and prosperity and keep pace with global changes, and there is no doubt that the most important means in order to achieve what we mentioned are human resources Which proceeds in accordance with legal and regulatory provisions, starting from employment to training and running the career path until the end of the job relationship.
Keywords: المؤسسات الإدارية -- القوى العاملة -- الجامعة الجزائرية -- فلسفة التسيير -- الوظيفة العمومية